Does The Productivity of Companies Affected by Employee Stock Option Plans and Intellectual Capital? - Elen Puspitasari; MG Kentris Indarti; Bambang Sudiyatno; Wahyu Meiranto (Jurnal Dinamika Akuntansi, 2024)
Purposes: This study tries to identify the impact of intellectual capital and employee stock option plans on company productivity. Productivity is measured with The Malmquist Productivity Index which is intended to measure the efficiency of companies. Measurement of intellectual capital using Value Added Intellectual Capital determined by human capital efficiency, structural capital efficiency and capital employed efficiency. Methods: This research uses a quantitative approach, and data collection is carried out through secondary data. The research sample was taken from 60 companies with 180 observation data from the financial industry sector listed on the Indonesia Stock Exchange from 2019 to 2021, during the Covid-19 pandemic. The multiple regression analysis method is used to examine the relationship between intellectual capital, employee stock option plans, and company productivity. Findings: The results imply that human capital, structural capital, capital employ and employee stock option plans have impact on company productivity. Therefore, a dominant factor affecting company productivity is human resources. The implementation of share ownership schemes for employees has not been widely used in businesses that operate in the Indonesian financial industry sector. Novelty: The advantage of the Malmquist Productivity Index on the financial industry when compared to others is that it does not require assumptions of corporate behavior as applied in the Data Envelopment Analysis methods such as minimizing costs or maximizing profits. The Malmquist Productivity Index can specifically assess the productivity of each company unit. This research became very interesting because the productivity measured by the Malmquist Index in the finance industry was influenced by structural capital and human capital.